2012
DOI: 10.5402/2012/732176
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Rheology of Polymer Melts: State of the Art

Abstract: The extreme sensitivity of rheology to the microstructure of polymer melts has prompted the development of "analytical rheology," which seeks inferring the structure and composition of an unknown sample based on rheological measurements. Typically, this involves the inversion of a model, which may be mathematical, computational, or completely empirical. Despite the imperfect state of existing models, analytical rheology remains a practically useful enterprise. I review its successes and failures in inferring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 342 publications
(425 reference statements)
1
14
0
Order By: Relevance
“…They found that their simulation results agreed with the Likhtman-McLeish theory [14] by using the double reptation approximation for the CR effect and removing high-frequency CLF contributions [15]. The related theories have also been extensively reviewed in the literature [7,[10][11][12][13][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 51%
“…They found that their simulation results agreed with the Likhtman-McLeish theory [14] by using the double reptation approximation for the CR effect and removing high-frequency CLF contributions [15]. The related theories have also been extensively reviewed in the literature [7,[10][11][12][13][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 51%
“…In order to consider these components in the calculation, a stepwise procedure is adopted. Since the polymer's architecture is also considered in this model, it is necessary to determine the viscosity ratio between a linear polymer used as reference and a (hyper)branched one which has the same total molecular weight [41][42][43][44][45][46]. Eq.…”
Section: Phase Viscositiesmentioning
confidence: 99%
“…The last two decades have seen an increasing level of interest in the synthesis of star, branched, and hyperbranched polymers because of the differentiated material properties that they exhibit compared to their linear counterparts. For example, they have shown significant potential to deliver differentiated application performance in areas such as melt flow, drug/gene delivery, and medical imaging . Branched structures are of particular interest in the case of biosourced polymers because: (a) they are typically more sensitive to processing conditions, e.g., temperature, and/or (b) the physical properties of linear biopolymers are often on the limit of viability for use in many medical, healthcare, and pharma applications …”
Section: Introductionmentioning
confidence: 99%
“…The last two decades have seen an increasing level of interest in the synthesis of star, branched, and hyperbranched polymers because of the differentiated material properties that they exhibit compared to their linear counterparts. For example, they have shown signifi cant potential to deliver differentiated application performance in areas such as melt fl ow, [1][2][3] drug/gene delivery, [4][5][6] and medical imaging. [7][8][9] Branched structures are of particular media dielectric properties could be used to follow ROP reactions in real time.…”
Section: Introductionmentioning
confidence: 99%